INFORMATION DISORDER IN TIMES OF CRISIS: SCOPE REVIEW PROTOCOL - Pinto, Vanessa Santos Silva Corrêa; dos Santos, Marcia Rodrigues; Pinto, Daniel Motta Corrêa; da Silva, Carlos Roberto Lyra; Valente, Tania Cristina Oliveira; Antunes, Maria João Lopes (Seven Editora, 2025)
Objective: to map the literature on information disorder faced by the population during the COVID-19 pandemic. Method: the protocol will follow the methodological proposal designated by the Joanna Briggs Institute (JBI) and the recommendations for developing scoping reviews from the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols - extension for scoping reviews (PRISMA-ScR). Searches will be conducted in the following databases: LILACS, PUBMED, MEDLINE, EMBASE, and SCOPUS, WEB OF SCIENCE, and in the gray literature in the Theses and Dissertations Database of the Coordination for the Improvement of Higher Education Personnel (CAPES). A search strategy was developed and adapted for each database, from 2020 to 2025, with no language restrictions, full text. Articles will be selected by two independent reviewers. Results: data will be extracted from the selected articles using a standardized form. The full texts of the included articles will be read and analyzed according to the eligibility criteria. The results will be presented in a flowTable and narrative summary, following the PRISMA-ScR guidelines. Conclusion:  the scoping review generated through this protocol is expected to present the general state of scientific evidence and identify gaps that need further study on the topic under investigation.DOI: https://doi.org/10.56238/sevened2025.029-117